Axiological status of social capital in the structure of intangible resources of contemporary society - Dedolko, Julia V. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
The article analyses the structure, the main factors in the formation of social capital, as well as the prerequisites for the emergence of its concept in modern social science. Structural elements of social capital, their place in the system of intangible resources of society are revealed. The article author has distinguished and characterised the basic projections of social capital (societal, axiological and institutional) and their parameters. The significant status of social capital in the transition of contemporary society to the post-industrial stage context had substantiated (P. Bourdieu, J. Coleman, R. Putnam, F. Fukuyama, D. M. Bulynko, A. N. Danilov, D. G. Rotman, A. I. Zelenkov, V. T. Novikov). Systemic analysis of contemporary Belarusian society’s social capital dynamics had performed.
Keywords: social capital; society; institutions; values; norms; traditions; trust; cooperation; solidarity; cohesion